ANALYSIS OF GROUND COFFEE BUSINESS IN REJANG LEBONG DISTRICT ANALISIS USAHA KOPI BUBUK DI KABUPATEN REJANG LEBONG - Febri Nur Pramudya; Gracia Gabrienda; Hety Novitasari (Sekolah Tinggi Pariwisata Mataram, 2021)
Robusta coffee powder processing techniques greatly affect the value of production, the greater the value of coffee powder is not necessarily able to provide big profits for the businessman, because the value of production is strongly influenced by the selling price and production of Robusta coffee powder in each processing. This research was conducted at UD. Cap Gentong Mas. This study aims to determine the magnitude of the benefits obtained in the robusta coffee powder processing business at UD. Cap Gentong Mas. The method used is purposive (intentional), with the criteria of one business that has been established for more than fifteen years with data collection techniques using primary data and secondary data and income analysis methods and efficiency values. Benefits obtained at UD. Gentong Mas Cap is Rp. 5,376,077 / month. The acquisition of efficiency value is 1.2, meaning that the business has advantages and can be developed.